Law Implementation Of The National Health Insurance Program (JKN) For Medical Acupunture Specialist Services In Kayuagung Regional General Hospital - Edi Suhaimi; Joni Emirzon (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Termination of health service coverage for medical acupuncture by BPJS in January 2015 on the grounds that medical acupuncture includes traditional health services contained in Presidential Decree number 12 of 2013 article 25 (j). Previously, medical acupuncture services had been guaranteed by PT. Askes based onjoint regulation of the Minister of Health and Minister of Home Affairs number 138 and 12 of 2009.This study uses an empirical legal approach and a review of laws and regulations related to health insurance. Results: There are 2 regulations for acupuncture services, namely traditional acupuncture performed by non-medical personnel, and medical acupuncture performed by medical personnel (acupuncture specialists or general practitioners plus). Medical acupuncture services in hospitals performed by acupuncture specialists are medical services which include: examination and diagnosis, treatment and non-surgical specialist medical treatment according to medical indications, as contained in the fourth revision of Presidential Regulation number 12 of 2013 namely Ppresidential decree number 82 of 2018 on article 47 paragraph (1) points b3 and b4. Also in line with the previous regulation, namely Regulation of the Minister of Health number 28 of 2014 concerning guarantees for medical acupuncture services. Conclusion: Based on the principle of Lex specialis derogate legi generalis, the Perpres can be the basis for implementing JKN for medical acupuncture services in hospitals